Eksplorasi Parenting Self Efficacy terhadap Resiliensi Ibu dari Anak dengan Autism Spectrum Disorders - Nuraini Isnanidiyanti, Wahyu; Saloko, Erayanti (Jurnal Terapi Wicara dan Bahasa, 2023)
Abstract   Background. The presence of an ASD child in the family has an impact on their daily life. The many difficulties and obstacles to raising ASD children will bring about a sense of confidence and the ability to rise from these difficulties. This study aims to find out in more detail the difficulties experienced by mothers when raising children and how parenting self-efficacy affects the resilience of mothers with ASD children. Methods Of Study. This type of research is phenomenological research and the data analysis method used is thematic analysis techniques by conducting interviews with 7 mothers of ASD children. Data collection tool in the form of informed consent and interview protocol. Result. Based on the thematic data analysis, 3 themes have been obtained: (1) Parenting self-efficacy for mothers with ASD children (2) Resilience for mothers with ASD children (3) Parenting self-efficacy for the resilience of mothers with ASD children. The three major themes are supported by the presence of sub-themes in them. Conclusion. The importance of parenting self-efficacy which affects resilience has a positive impact on the lives of mothers with ASD children. So that it will bring joy to the mother and increase the resilience of the mother in caring for children with ASD. Benefits for family members and children with ASD will also be felt if the mother has both abilities. Life in the family will be better and prosperous even with the presence of an ASD child.   Keywords: ASD mother, parenting self efficacy, resilience